Polymer-ceramic composite dielectric material, preparation method and application in capacitor
By preparing modified boron nitride nanorods and europium-doped barium titanate@ZIF-67 ceramic matrix composite filler, combined with hot pressing molding technology, the problem of poor compatibility of nanofillers in the existing technology is solved, and high-incidence is achieved Polymer-ceramic composite dielectric material with electrical constant, breakdown strength and energy storage density.
Patent Information
- Application Number
- CN202411571326.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Among the existing polymer-based ceramic composite dielectric materials, the nanobarium titanate filler has poor compatibility with polyvinylidene fluoride, resulting in aggregation and structural defects, which in turn affects the breakdown strength and energy storage density.
Boron nitride nanorods were prepared by boric acid and melamine, and modified by polydopamine, combined with europium-doped barium titanate @ZIF-67 and modified boron nitride nanorods to form a ceramic matrix composite filler, and obtained by hot pressing A three-layer structure polymer-ceramic composite dielectric material.
The dielectric constant, breakdown strength and energy storage density are improved, the dielectric loss is reduced, and the heat resistance and dispersion of the material are enhanced.
Smart Images

Figure CN119431900A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of layered product materials, in particular to a polymer-ceramic composite dielectric material, a preparation method and application in capacitors. Background Art
[0002] Among the many energy storage technologies, dielectric energy storage has the advantages of high power density, fast charge and discharge rate, low cost, long life and high working voltage, and is widely used in pulse power supply systems and power and electrical fields. Dielectric materials are the core of dielectric energy storage. At present, inorganic ceramic materials, organic polymer materials and polymer-ceramic nanocomposites are several types of dielectric energy storage materials that have attracted much attention. Inorganic ceramic dielectric materials have good temperature stability and high dielectric constant, but their breakdown strength is relatively low. Organic polymer materials have high breakdown strength, but their dielectric constant is very low, which will lead to low energy storage density of dielectric materials. Polymer-ceramic nanocomposites have the respective characteristics of organic polymer materials and inorganic ceramic materials, and realize the coordinated regulation of the dielectric constant and breakdown strength of the composite material, thereby improving its energy storage density.
[0003] For example, Chinese patent CN102173155B provides a polymer-based ceramic composite dielectric material, characterized in that it is composed of multiple dielectric material layers, the multiple dielectric material layers including: a first polyvinylidene fluoride layer; and a composite material layer, the composite material layer is arranged on one side surface of the first polyvinylidene fluoride layer and contains 90-50vol% polyvinylidene fluoride and 10-50vol% nano barium titanate. However, the inorganic nano barium titanate filler in this polymer-based ceramic composite dielectric material has poor compatibility with polyvinylidene fluoride, which will inevitably cause serious aggregation, thereby generating structural defects, which will lead to the formation of leakage current channels and a decrease in breakdown strength under high voltage. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a method for preparing a polymer-ceramic composite dielectric material, comprising the following steps:
[0005] Step (1), preparing boron nitride nanorods using boric acid and melamine as raw materials, and then modifying with polydopamine to obtain surface-modified boron nitride nanorods;
[0006] Step (2), preparing europium-doped barium titanate using barium carbonate, titanium dioxide and europium oxide as raw materials, and treating with polyvinyl pyrrolidone to obtain pretreated europium-doped barium titanate; and then preparing europium-doped barium titanate@ZIF-67 using pretreated europium-doped barium titanate, cobalt nitrate hexahydrate and 2-methylimidazole as raw materials;
[0007] Europium-doped barium titanate@ZIF-67 was modified with 3-glycidyloxypropyltrimethoxysilane and then combined with surface-modified boron nitride nanorods to obtain a ceramic-based composite filler; the ceramic-based composite filler was modified with 4-cyano-1-butanethiol to obtain a modified ceramic-based composite filler;
[0008] Step (3), reacting pullulan with 2-chloro-5-(trifluoromethyl)benzoyl chloride to obtain modified pullulan; reacting glycidyl-cage polysilsesquioxane with modified pullulan to obtain composite modified pullulan;
[0009] Adding the composite modified pullulan and the modified composite nanosheets into N,N-dimethylformamide to obtain a mixed solution A, casting the mixed solution into a film to obtain an outer film;
[0010] Adding the composite modified pullulan and the modified ceramic-based composite filler into N,N-dimethylformamide to obtain a mixed solution B, casting the mixed solution into a film, and obtaining an inner layer film;
[0011] The inner film is sandwiched between the outer films, hot-pressed and then cooled to obtain a polymer-ceramic composite dielectric material with a three-layer structure.
[0012] Preferably, in the step (1), the preparation method of the surface-modified boron nitride nanorods is as follows: adding boric acid to deionized water, stirring at 70-80°C until completely dissolved, then adding melamine, stirring at a speed of 400-500r / min for 20-40min, and then drying at 60-80°C for 10-16h to obtain a white solid; heating the white solid to 900-1100°C in a nitrogen atmosphere at a heating rate of 5°C / min, calcining for 3-5h, and naturally cooling to room temperature to obtain boron nitride nanorods; wherein the mass ratio of boric acid, deionized water, and melamine is (4-6):(100-120):(2.7-5.4);
[0013] Adding boron nitride nanorods to Tris-HCl buffer, adjusting the pH to 7.8-8.5 with a 0.1 mol / L sodium hydroxide aqueous solution, ultrasonically dispersing for 1-3 hours, then adding dopamine hydrochloride, stirring for 10-15 hours, centrifuging, washing, and drying to obtain surface-modified boron nitride nanorods; wherein the amount ratio of boron nitride nanorods, Tris-HCl buffer, and dopamine hydrochloride is (0.4-1) g: (200-500) mL: (0.8-2) g;
[0014] In the above process, boron nitride nanorods are prepared with boric acid and melamine as raw materials, and then modified with polydopamine in an alkali to obtain surface-modified boron nitride nanorods, thereby introducing phenolic hydroxyl groups and amino groups on the surface of the boron nitride nanorods.
[0015] Preferably, in the step (2), the preparation method of the europium-doped barium titanate @ZIF-67 is as follows: barium carbonate, titanium dioxide and europium oxide are mixed and ground for 10-20 minutes, then ground with ethanol for 30-50 minutes, and then dried at 35-45°C for 5-7 hours to obtain a mixed precursor, wherein the mass ratio of barium, europium and titanium in the mixed precursor is 13.1:(0.2-0.4):4.8; the mixed precursor is heated to 950-1050°C at a heating rate of 5°C / min and calcined for 11-13 hours, and then cooled to room temperature at a cooling rate of 5°C / min, and the above calcination process is repeated 2-3 times, and ground to obtain europium-doped barium titanate;
[0016] The europium-doped barium titanate is added to ethanol and ultrasonically dispersed for 50-80 minutes, polyvinyl pyrrolidone is added, and ultrasonic dispersion is continued for 60-90 minutes, and then stirred at a speed of 500-600 r / min at room temperature for 3-4 hours, centrifuged, washed, and dried to obtain pretreated europium-doped barium titanate; wherein the mass ratio of europium-doped barium titanate, ethanol, and polyvinyl pyrrolidone is (3-5):(400-500):(5-10);
[0017] The pretreated europium-doped barium titanate was added to methanol for ultrasonic dispersion for 50-80 minutes, cobalt nitrate hexahydrate was added, and the mixture was stirred at a speed of 500-600 r / min for 1-1.5 hours, and then a 2-methylimidazole / methanol solution with a concentration of 0.066 g / mL was added, and the mixture was stirred for reaction at room temperature for 22-26 hours, centrifuged, washed and dried to obtain europium-doped barium titanate@ZIF-67; wherein the mass ratio of the pretreated europium-doped barium titanate, methanol, cobalt nitrate hexahydrate, and 2-methylimidazole / methanol solution is (4-6):(400-500):(29.1-49.5 g):(428-715);
[0018] In the above process, barium carbonate, titanium dioxide and europium oxide are used as reaction raw materials to prepare europium-doped barium titanate; then cobalt nitrate hexahydrate and 2-methylimidazole are used as raw materials to generate a ZIF-67 buffer layer on the surface of the europium-doped barium titanate, and the europium-doped barium titanate is treated with polyvinyl pyrrolidone so that the europium-doped barium titanate can be evenly distributed in ZIF-67.
[0019] Preferably, in the step (2), the preparation method of the modified ceramic-based composite filler is as follows: 3-glycidyloxypropyltrimethoxysilane and europium-doped barium titanate @ZIF-67 are dispersed in ethanol, and then refluxed for 4-6 hours at a temperature of 75-80°C and a pH of 4-10, and the precipitate is collected, washed and dried to obtain epoxy-functionalized europium-doped barium titanate @ZIF-67; wherein the mass ratio of 3-glycidyloxypropyltrimethoxysilane, europium-doped barium titanate @ZIF-67, and ethanol is (0.4-0.8):(3-5):(100-120);
[0020] Adding epoxy-functionalized europium-doped barium titanate @ZIF-67 to tetrahydrofuran, and then adding surface-modified boron nitride nanorods, stirring and reacting at 55-65°C for 3.5-4.5h, and removing the solvent by reduced pressure distillation at 40-50°C to obtain a ceramic-based composite filler; wherein the mass ratio of epoxy-functionalized europium-doped barium titanate @ZIF-67, tetrahydrofuran, and surface-modified boron nitride nanorods is (0.5-0.9):(80-100):(4-8);
[0021] The ceramic-based composite filler is added to dimethyl sulfoxide, ultrasonically treated for 20-40 minutes, and then 4-cyano-1-butanethiol and triethylamine are added, and the reaction is stirred at 75-85° C. for 5-7 hours. After the reaction is completed, centrifugation is performed, and the obtained solid product is washed with dimethyl sulfoxide and then dried to obtain a modified ceramic-based composite filler; wherein the mass ratio of the ceramic-based composite filler, dimethyl sulfoxide, 4-cyano-1-butanethiol, and triethylamine is (5-7):(100-120):(5.8-11.5):(0.05-0.1);
[0022] In the above process, europium doped barium titanate @ZIF-67 reacts with 3-glycidyloxypropyltrimethoxysilane to introduce epoxy groups on the surface of europium doped barium titanate @ZIF-67 to obtain epoxy-functionalized europium doped barium titanate @ZIF-67; the epoxy groups on the surface of epoxy-functionalized europium doped barium titanate @ZIF-67 are ring-opened and reacted with amino groups on the surface of surface-modified boron nitride nanorods, and the epoxy-functionalized europium doped barium titanate @ZIF-67 is deposited on the surface-modified boron nitride nanorods to obtain a ceramic-based composite filler; the remaining epoxy groups on the surface of the ceramic-based composite filler are ring-opened and reacted with the thiol groups of 4-cyano-1-butanethiol to introduce cyano groups on the surface of the ceramic-based composite filler.
[0023] Preferably, in step (3), the preparation method of the composite modified pullulan is as follows: at 80-90° C., pullulan and N,N-dimethylacetamide are mixed in a mass ratio of (1.3-2.6):(50-100), and stirred for 20-40 minutes to obtain a pullulan mixed solution; 2-chloro-5-(trifluoromethyl)benzoyl chloride and N,N-dimethylacetamide are diluted and mixed in a mass ratio of (0.03-0.06):(3-5), and stirred in an ice water bath. At the same time, the mixture is added dropwise into the pullulan mixture at a speed of 0.5-1.5 mL / min, first reacted in an ice-water bath for 1.5-2.5 h, then reacted at room temperature for 3.5-4.5 h, and after the reaction, the reactant is concentrated by rotary evaporation to half of the original volume, and then the product is precipitated with acetone, washed, and dried to obtain modified pullulan; wherein the mass ratio of pullulan to 2-chloro-5-(trifluoromethyl)benzoyl chloride is (1.3-2.6):(0.03-0.06);
[0024] Add glycidyl-cage polysilsesquioxane to tetrahydrofuran, then add modified pullulan, heat to reflux for 6-8h, and remove the solvent by reduced pressure distillation at 40-50°C to obtain composite modified pullulan; wherein the mass ratio of glycidyl-cage polysilsesquioxane, tetrahydrofuran, and modified pullulan is (0.05-0.1):(30-50):(1-2);
[0025] In the above process, the acyl chloride group of 2-chloro-5-(trifluoromethyl)benzoyl chloride reacts with a small amount of hydroxyl groups of pullulan to introduce cyano groups, benzene rings and hydrophobic trifluoromethyl groups into pullulan, which is then modified by glycidyl-cage polysilsesquioxane (OG-POSS). The epoxy groups of OG-POSS react with part of the hydroxyl groups of the modified pullulan to introduce the POSS structure into the modified pullulan.
[0026] Preferably, in the step (3), the outer film is prepared by mixing the composite modified pullulan, the modified composite nanosheets and N,N-dimethylformamide in a mass ratio of (3-6):(0.06-0.09):(100-200), stirring at room temperature for 10-16 hours to obtain a mixed solution A; pouring the mixed solution A on a glass plate and preheating it at 38-42°C for 1-1.5 hours, then drying it at 80-90°C for 8-10 hours, and then annealing it at 115-125°C for 10-14 hours to obtain an outer film with a thickness of 5-8 μm;
[0027] The preparation method of the inner film comprises the following steps: mixing a composite modified pullulan, a modified ceramic-based composite filler and N,N-dimethylformamide in a mass ratio of (3-6):(0.08-1.2):(100-200), stirring at room temperature for 10-16 hours to obtain a mixed solution B; pouring the mixed solution B on a glass plate and preheating at 38-42° C. for 1-1.5 hours, then drying at 80-90° C. for 8-10 hours, and then annealing at 115-125° C. for 10-14 hours to obtain an inner film with a thickness of 5-8 μm.
[0028] Preferably, in step (3), the hot pressing molding conditions are: hot pressing temperature is 180-200°C, hot pressing pressure is 15-20Mpa, and hot pressing time is 20-30min.
[0029] Furthermore, in step (3), the method for preparing the modified composite nanosheet comprises the following steps:
[0030] Step S1, preparing a zinc acetate aqueous solution with a concentration of 0.06 mol / L and a sodium hydroxide aqueous solution with a concentration of 1.25 mol / L, and under stirring, dripping the sodium hydroxide aqueous solution into the zinc acetate aqueous solution at a rate of 0.5-1.5 mL / min, standing and settling for 5-7 hours, centrifuging, washing, and drying to obtain zinc oxide nanosheets; wherein the volume ratio of the sodium hydroxide aqueous solution to the zinc acetate aqueous solution is (2-2.8):(9-24);
[0031] Add zinc oxide nanosheets to a 1.5 mol / L copper acetate aqueous solution, stir for 20-40 min, filter, and calcine the resulting solid product in air at 280-320° C. for 1.5-2.5 h to obtain composite nanosheets; wherein the amount ratio of zinc oxide nanosheets to copper acetate aqueous solution is (3-8) g: (50-80) mL;
[0032] In the above process, n-type zinc oxide nanosheets were prepared using zinc acetate water and sodium hydroxide as raw materials, and then the zinc oxide nanosheets were immersed in a copper acetate aqueous solution, and p-type nano copper oxide was deposited on the surface of the zinc oxide nanosheets after calcination to obtain a composite nanosheet with a pnp heterostructure.
[0033] Step S2, adding the composite nanosheets to a methanol aqueous solution, then adding (3-mercaptopropyl)trimethoxysilane, ultrasonically treating for 20-40 minutes, reflux reacting at 65-75° C. for 1.5-2.5 hours, centrifuging, washing and drying to obtain functionalized composite nanosheets; wherein the mass ratio of methanol to water in the methanol aqueous solution is 7:2; the mass ratio of the composite nanosheets, the methanol aqueous solution and (3-mercaptopropyl)trimethoxysilane is (3-5):(74.6-112):(10-15);
[0034] The functionalized composite nanosheets are added to ethanol, ultrasonically dispersed for 20-40 minutes, heated to 50-80°C, and then 5-hexenoic acid and azobisisobutyronitrile are added, stirred for reaction for 3-5 hours, and after the reaction is completed, centrifuged, washed, and dried to obtain modified composite nanosheets; wherein the mass ratio of the functionalized composite nanosheets, ethanol, 5-hexenoic acid, and azobisisobutyronitrile is (4-8):(80-100):(0.4-1.6):(0.08-0.1);
[0035] In the above process, the composite nanosheets are treated with (3-mercaptopropyl)trimethoxysilane to introduce mercapto functional groups on their surfaces to form functionalized composite nanosheets; the mercapto groups on the surfaces of the functionalized composite nanosheets react with the carbon-carbon double bonds of 5-hexenoic acid to introduce organic chains and carboxyl groups on the surfaces of the composite nanosheets.
[0036] The polymer-ceramic composite dielectric material is prepared by the method for preparing the polymer-ceramic composite dielectric material.
[0037] Application of the polymer-ceramic composite dielectric material in capacitors.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] 1. The present invention uses bio-pullulan as a raw material to prepare a biomass-based dielectric polymer, and uses it as a film-forming material for an inner film and an outer film. Traditional organic dielectric polymer films are derived from petroleum. Therefore, compared with traditional technologies, the method of the present invention reduces the use of mineral energy, and the biomass-based dielectric polymer film has the advantages of being renewable and biodegradable. The present invention modifies pullulan by 2-chloro-5-(trifluoromethyl)benzoyl chloride, and introduces cyano and trifluoromethyl polar groups to improve the dielectric constant of pullulan. The reduction of hydrophilic hydroxyl groups and the reduction of hydrophobic trifluoromethyl groups in the modification process can improve the dielectric constant of pullulan. The introduction of fluoromethyl groups leads to low hygroscopicity, which helps to reduce dielectric loss, thereby improving energy storage performance and breakdown strength; the introduction of benzene rings can improve the heat resistance of pullulan polysaccharide; further, a POSS structure is introduced into the modified pullulan polysaccharide; the low polarizability of POSS helps to further reduce dielectric loss; the cage structure and functional groups of POSS are conducive to the formation of defects and traps, thereby improving the dielectric constant and breakdown strength; and the heat-resistant rigid skeleton of POSS improves the heat resistance of the inner film and the outer film; therefore, the polymer-ceramic composite dielectric material of the present invention still maintains excellent performance at high temperatures.
[0040] 2. Modified composite nanosheets are added as fillers in the outer film of the polymer-ceramic composite dielectric material of the present invention. The modified composite nanosheets are obtained by modifying the composite nanosheets with (3-mercaptopropyl)trimethoxysilane and 5-hexenoic acid. The pnp heterostructure of the composite nanosheets helps to reduce the dielectric loss of the outer film and improve its breakdown strength, dielectric constant and energy storage performance. After the composite nanosheets are modified, carboxyl groups and organic chains are introduced. The carboxyl groups are combined with the cyano groups in the composite modified pullulan polysaccharide through strong electrostatic interaction, thereby improving the dispersibility and interface compatibility between the modified composite nanosheets and the modified pullulan polysaccharide. The organic chains are cross-linked with the composite modified pullulan polysaccharide to increase the cross-linking density of the outer film, thereby improving its heat resistance.
[0041] 3. The present invention adds a modified ceramic-based composite filler to a composite modified pullulan to prepare an inner layer film. The modified ceramic-based composite filler is obtained by modifying the ceramic-based composite filler with 4-cyano-1-butanethiol. 4-cyano-1-butanethiol introduces cyano groups on the surface of the ceramic-based composite filler, which are covalently cross-linked with the cyano groups in the composite modified pullulan during heating, thereby improving the dispersibility and interface compatibility between the ceramic-based composite filler and the modified pullulan.
[0042] 4. The ceramic-based composite filler of the present invention is formed by combining epoxy-functionalized europium-doped barium titanate @ZIF-67 with surface-modified boron nitride nanorods: barium titanate is a ceramic filler with excellent dielectric properties. Doping europium therein can improve the dielectric properties of barium titanate-based ceramic materials, and then a ZIF-67 buffer layer is generated on the surface of europium-doped barium titanate. The spatial immobilization effect of ZIF-67 effectively alleviates the aggregation of europium-doped barium titanate nanoparticles, and can prevent the propagation of electrical trees, improve the performance of the inner film, and then improve the dielectric properties and energy storage performance of the polymer-ceramic composite dielectric material; boron nitride nanomaterials have high insulation and pressure resistance, can improve the dielectric constant, breakdown strength and energy storage performance of the inner film, and reduce dielectric loss. In addition, due to the thermal conductivity of boron nitride nanorods, the heat dissipation effect of the inner film can be improved, and the influence of temperature on the performance of the inner film can be reduced, thereby giving the polymer-ceramic composite dielectric material better dielectric properties and heat resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 It is a process flow chart of the preparation method of the polymer-ceramic composite dielectric material of the present invention;
[0044] Figure 2 It is a comparison chart of dielectric constant tests of polymer-ceramic composite dielectric materials prepared in Examples 2-4 of the present invention and Comparative Examples 1-8 at different temperatures;
[0045] Figure 3 It is a comparison chart of the breakdown strength test of the polymer-ceramic composite dielectric materials prepared in Examples 2-4 of the present invention and Comparative Examples 1-8 at different temperatures;
[0046] Figure 4 It is a comparison chart of the maximum discharge energy density test of the polymer-ceramic composite dielectric materials prepared by Examples 2-4 of the present invention and Comparative Examples 1-8. DETAILED DESCRIPTION
[0047] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0048] Example 1
[0049] This embodiment discloses a method for preparing a modified composite nanosheet, comprising the following steps:
[0050] Step S1, preparing a zinc acetate aqueous solution with a concentration of 0.06 mol / L and a sodium hydroxide aqueous solution with a concentration of 1.25 mol / L, under stirring conditions, dropping 2.4 mL of the sodium hydroxide aqueous solution into 16 mL of the zinc acetate aqueous solution at a speed of 1 mL / min, standing for precipitation for 6 hours, centrifuging, washing the obtained solid product with deionized water for 7 times, and vacuum drying at 70° C. to obtain zinc oxide nanosheets; adding 5.5 g of the zinc oxide nanosheets into 65 mL of a copper acetate aqueous solution with a concentration of 1.5 mol / L, stirring for 30 minutes, filtering, and calcining the obtained solid product in air at 300° C. for 2 hours to obtain composite nanosheets;
[0051] Step S2, adding 4 g of the composite nanosheet to 93.3 g of methanol aqueous solution, and then adding 12.5 g of (3-mercaptopropyl)trimethoxysilane, after ultrasonic treatment for 30 min, reflux reaction at 70° C. for 2 h, centrifugation, washing the obtained solid product with toluene and drying to obtain functionalized composite nanosheets; wherein the mass ratio of methanol to water in the methanol aqueous solution is 7:2;
[0052] 6 g of functionalized composite nanosheets were added to 90 g of ethanol, ultrasonically dispersed for 30 min, heated to 65 °C, and then 1 g of 5-hexenoic acid and 0.09 g of azobisisobutyronitrile were added, stirred and reacted for 4 h. After the reaction was completed, centrifuged, washed, and vacuum dried at 75 °C to obtain modified composite nanosheets.
[0053] Example 2
[0054] This embodiment discloses a method for preparing a polymer-ceramic composite dielectric material, comprising the following steps:
[0055] Step (1), adding 4 g of boric acid to 100 g of deionized water, stirring at 70° C. until completely dissolved, then adding 2.7 g of melamine, stirring at a speed of 400 r / min for 40 min, and then drying at 60° C. for 16 h to obtain a white solid; heating the white solid to 900° C. in a nitrogen atmosphere at a heating rate of 5° C. / min, calcining for 5 h, and naturally cooling to room temperature to obtain boron nitride nanorods;
[0056] 0.4 g of boron nitride nanorods were added to 200 mL of Tris-HCl buffer, and the pH was adjusted to 7.8 with a 0.1 mol / L sodium hydroxide aqueous solution, and ultrasonically dispersed for 1 h, and then 0.8 g of dopamine hydrochloride was added, stirred for 10 h, and centrifuged. The obtained solid product was washed with deionized water and vacuum dried at 50 ° C for 24 h to obtain surface-modified boron nitride nanorods;
[0057] Step (2), mixing barium carbonate, titanium dioxide and europium oxide and grinding them for 10 minutes, then grinding them with ethanol for 30 minutes, and then drying them at 35°C for 7 hours to obtain a mixed precursor, wherein the mass ratio of barium, europium and titanium in the mixed precursor is 13.1:0.4:4.8; heating the mixed precursor to 950°C at a heating rate of 5°C / min and calcining it for 13 hours, then cooling it to room temperature at a cooling rate of 5°C / min, repeating the above calcination process twice, and grinding to obtain europium-doped barium titanate;
[0058] 3 g of europium-doped barium titanate was added to 400 g of ethanol and ultrasonically dispersed for 50 min, 5 g of polyvinyl pyrrolidone was added, and ultrasonication was continued for 60 min, and then stirred at a speed of 500 r / min for 4 h at room temperature, centrifuged, and the obtained solid product was washed with methanol and dried at 50° C. for 14 h to obtain pretreated europium-doped barium titanate;
[0059] 4 g of pretreated europium-doped barium titanate was added to 400 g of methanol and ultrasonically dispersed for 50 min. 29.1 g of cobalt nitrate hexahydrate was added and stirred at 500 r / min for 1.5 h. 428 g of 0.066 g / mL 2-methylimidazole / methanol solution was added and stirred at room temperature for 22 h. The mixture was centrifuged and the precipitate was washed with ethanol and deionized water in turn and dried at 50 °C for 14 h to obtain europium-doped barium titanate@ZIF-67.
[0060] 0.4 g of 3-glycidyloxypropyltrimethoxysilane and 3 g of europium-doped barium titanate @ZIF-67 were dispersed in 100 g of ethanol, and then refluxed for 6 h at 75 ° C and pH 4. The precipitate was collected, washed and dried to obtain epoxy-functionalized europium-doped barium titanate @ZIF-67.
[0061] 0.5 g of epoxy-functionalized europium-doped barium titanate @ZIF-67 was added to 80 g of tetrahydrofuran, and then 4 g of surface-modified boron nitride nanorods were added, and the mixture was stirred at 55°C for 4.5 h, and the solvent was removed by reduced pressure distillation at 40°C to obtain a ceramic-based composite filler;
[0062] 5 g of a ceramic-based composite filler was added to 100 g of dimethyl sulfoxide, and ultrasonic treatment was performed for 20 min. Then, 5.8 g of 4-cyano-1-butanethiol and 0.05 g of triethylamine were added, and the mixture was stirred and reacted at 75° C. for 7 h. After the reaction was completed, the mixture was centrifuged, and the obtained solid product was washed with dimethyl sulfoxide and then dried to obtain a modified ceramic-based composite filler.
[0063] Step (3), adding 1.3 g of pullulan to 50 g of N, N-dimethylacetamide at 80° C. and stirring for 20 min to obtain a pullulan mixed solution; diluting 0.03 g of 2-chloro-5-(trifluoromethyl)benzoyl chloride with 3 g of N, N-dimethylacetamide, and dripping it into the pullulan mixed solution at a rate of 0.5 mL / min in an ice-water bath while stirring, first reacting in an ice-water bath for 1.5 h, and then reacting at room temperature for 3.5 h. After the reaction is completed, the reactant is concentrated by rotary evaporation to half of the original volume, and then the product is precipitated with acetone, washed, and dried to obtain a modified pullulan;
[0064] 0.05 g of glycidyl-cage polysilsesquioxane was added to 30 g of tetrahydrofuran, and then 1 g of modified pullulan was added, the temperature was raised to reflux reaction for 6 hours, and the solvent was removed by reduced pressure distillation at 40° C. to obtain a composite modified pullulan;
[0065] 3 g of composite modified pullulan and 0.06 g of modified composite nanosheets were added to 100 g of N,N-dimethylformamide and stirred at room temperature for 10 h to obtain a mixed solution A; the mixed solution A was poured onto a glass plate and preheated at 38° C. for 1.5 h, then dried at 80° C. for 10 h to evaporate the solvent, and then annealed at 115° C. for 14 h to obtain an outer film with a thickness of 5 μm;
[0066] 3 g of composite modified pullulan and 0.08 g of modified ceramic-based composite filler were added to 100 g of N,N-dimethylformamide and stirred at room temperature for 10 h to obtain a mixed solution B; the mixed solution B was poured on a glass plate and preheated at 38° C. for 1.5 h, then dried at 80° C. for 10 h to evaporate the solvent, and then annealed at 115° C. for 14 h to obtain an inner layer film with a thickness of 5 μm;
[0067] The inner film is sandwiched between the outer films, hot-pressed and then cooled to obtain a polymer-ceramic composite dielectric material with a three-layer structure; the hot-pressing temperature is 180° C., the hot-pressing pressure is 15 MPa, and the hot-pressing time is 30 min.
[0068] Example 3
[0069] This embodiment discloses a method for preparing a polymer-ceramic composite dielectric material, comprising the following steps:
[0070] Step (1), adding 6 g of boric acid to 120 g of deionized water, stirring at 80° C. until completely dissolved, then adding 5.4 g of melamine, stirring at a speed of 500 r / min for 20 min, and then drying at 80° C. for 10 h to obtain a white solid; heating the white solid to 1100° C. in a nitrogen atmosphere at a heating rate of 5° C. / min, calcining for 3 h, and naturally cooling to room temperature to obtain boron nitride nanorods;
[0071] 1 g of boron nitride nanorods was added to 500 mL of Tris-HCl buffer, and the pH was adjusted to 8.5 with a 0.1 mol / L sodium hydroxide aqueous solution, and ultrasonically dispersed for 3 h, and then 2 g of dopamine hydrochloride was added, stirred for 15 h, and centrifuged. The obtained solid product was washed with deionized water and vacuum dried at 60 ° C for 20 h to obtain surface-modified boron nitride nanorods;
[0072] Step (2), mixing barium carbonate, titanium dioxide and europium oxide and grinding them for 20 minutes, then grinding them with ethanol for 50 minutes, and then drying them at 45°C for 5 hours to obtain a mixed precursor, wherein the mass ratio of barium, europium and titanium in the mixed precursor is 13.1:0.2:4.8; heating the mixed precursor to 1050°C at a heating rate of 5°C / min and calcining it for 11 hours, then cooling it to room temperature at a cooling rate of 5°C / min, repeating the above calcination process 3 times, grinding, and obtaining europium-doped barium titanate;
[0073] 5 g of europium-doped barium titanate was added to 500 g of ethanol and ultrasonically dispersed for 80 min, 10 g of polyvinyl pyrrolidone was added, and ultrasonication was continued for 90 min, and then stirred at a speed of 600 r / min for 3 h at room temperature, centrifuged, and the obtained solid product was washed with methanol and dried at 60° C. for 10 h to obtain pretreated europium-doped barium titanate;
[0074] 6 g of pretreated europium-doped barium titanate was added to 500 g of methanol and ultrasonically dispersed for 50 min, 49.5 g of cobalt nitrate hexahydrate was added, and the mixture was stirred at 600 r / min for 1 h. Then 715 g of 0.066 g / mL 2-methylimidazole / methanol solution was added, and the mixture was stirred at room temperature for 26 h. The mixture was centrifuged, and the precipitate was washed with ethanol and deionized water in turn, and dried at 70 ° C for 10 h to obtain europium-doped barium titanate @ ZIF-67;
[0075] 0.8 g of 3-glycidyloxypropyltrimethoxysilane and 5 g of europium-doped barium titanate @ZIF-67 were dispersed in 120 g of ethanol, and then refluxed for 4 h at 80 ° C and pH 10. The precipitate was collected, washed and dried to obtain epoxy-functionalized europium-doped barium titanate @ZIF-67.
[0076] 0.9 g of epoxy-functionalized europium-doped barium titanate @ZIF-67 was added to 100 g of tetrahydrofuran, and then 8 g of surface-modified boron nitride nanorods were added, and the mixture was stirred at 65°C for 3.5 h. The solvent was removed by reduced pressure distillation at 50°C to obtain a ceramic-based composite filler.
[0077] 7 g of the ceramic-based composite filler was added to 120 g of dimethyl sulfoxide, and ultrasonic treatment was performed for 40 min. Then, 11.5 g of 4-cyano-1-butanethiol and 0.1 g of triethylamine were added, and the mixture was stirred and reacted at 85° C. for 5 h. After the reaction was completed, the mixture was centrifuged, and the obtained solid product was washed with dimethyl sulfoxide and then dried to obtain a modified ceramic-based composite filler.
[0078] Step (3), adding 2.6 g of pullulan to 100 g of N, N-dimethylacetamide at 90° C. and stirring for 40 min to obtain a pullulan mixed solution; diluting 0.06 g of 2-chloro-5-(trifluoromethyl)benzoyl chloride with 5 g of N, N-dimethylacetamide, and dripping it into the pullulan mixed solution at a rate of 1.5 mL / min in an ice-water bath while stirring, first reacting in an ice-water bath for 2.5 h, and then reacting at room temperature for 4.5 h. After the reaction is completed, the reactant is concentrated by rotary evaporation to half of the original volume, and then the product is precipitated with acetone, washed, and dried to obtain a modified pullulan;
[0079] 0.1 g of glycidyl-cage polysilsesquioxane was added to 50 g of tetrahydrofuran, and then 2 g of modified pullulan was added, the temperature was raised to reflux reaction for 8 hours, and the solvent was removed by reduced pressure distillation at 50° C. to obtain a composite modified pullulan;
[0080] 6 g of composite modified pullulan and 0.09 g of modified composite nanosheets were added to 200 g of N,N-dimethylformamide and stirred at room temperature for 16 h to obtain a mixed solution A; the mixed solution A was poured on a glass plate and preheated at 42° C. for 1 h, then dried at 90° C. for 8 h to evaporate the solvent, and then annealed at 125° C. for 10 h to obtain an outer film with a thickness of 8 μm;
[0081] 6 g of composite modified pullulan and 1.2 g of modified ceramic-based composite filler were added to 200 g of N,N-dimethylformamide, and stirred at room temperature for 16 h to obtain a mixed solution B; the mixed solution B was poured on a glass plate and preheated at 42° C. for 1 h, then dried at 90° C. for 8 h to evaporate the solvent, and then annealed at 125° C. for 10 h to obtain an inner layer film with a thickness of 8 μm;
[0082] The inner film is sandwiched between the outer films, hot-pressed and then cooled to obtain a polymer-ceramic composite dielectric material with a three-layer structure; the hot-pressing temperature is 200° C., the hot-pressing pressure is 20 MPa, and the hot-pressing time is 20 min.
[0083] Example 4
[0084] This embodiment discloses a method for preparing a polymer-ceramic composite dielectric material, comprising the following steps:
[0085] Step (1), adding 5 g of boric acid to 110 g of deionized water, stirring at 75° C. until completely dissolved, then adding 4.1 g of melamine, stirring at a speed of 450 r / min for 30 min, and then drying at 70° C. for 13 h to obtain a white solid; heating the white solid to 1000° C. in a nitrogen atmosphere at a heating rate of 5° C. / min, calcining for 4 h, and naturally cooling to room temperature to obtain boron nitride nanorods;
[0086] 0.7 g of boron nitride nanorods were added to 350 mL of Tris-HCl buffer, and the pH was adjusted to 8 with a 0.1 mol / L sodium hydroxide aqueous solution, and ultrasonically dispersed for 2 h, and then 1.4 g of dopamine hydrochloride was added, stirred for 12 h, and centrifuged. The obtained solid product was washed with deionized water and vacuum dried at 55 ° C for 22 h to obtain surface-modified boron nitride nanorods;
[0087] Step (2), mixing barium carbonate, titanium dioxide and europium oxide and grinding them for 15 minutes, then grinding them with ethanol for 40 minutes, and then drying them at 40°C for 6 hours to obtain a mixed precursor, wherein the mass ratio of barium, europium and titanium in the mixed precursor is 13.1:0.3:4.8; heating the mixed precursor to 1000°C at a heating rate of 5°C / min and calcining it for 12 hours, then cooling it to room temperature at a cooling rate of 5°C / min, repeating the above calcination process 3 times, grinding, and obtaining europium-doped barium titanate;
[0088] 4 g of europium-doped barium titanate was added to 450 g of ethanol and ultrasonically dispersed for 70 min, 7.5 g of polyvinyl pyrrolidone was added, and ultrasonic dispersion was continued for 70 min, and then stirred at a speed of 550 r / min at room temperature for 3.5 h, centrifuged, and the obtained solid product was washed with methanol and dried at 5° C. for 12 h to obtain pretreated europium-doped barium titanate;
[0089] 5 g of pretreated europium-doped barium titanate was added to 450 g of methanol for ultrasonic dispersion for 70 min, 39.3 g of cobalt nitrate hexahydrate was added, and the mixture was stirred at a speed of 550 r / min for 1.2 h. Then, 571.5 g of 0.066 g / mL 2-methylimidazole / methanol solution was added, and the mixture was stirred at room temperature for 24 h. The mixture was centrifuged, and the precipitate was washed with ethanol and deionized water in turn, and dried at 60 ° C for 12 h to obtain europium-doped barium titanate @ ZIF-67;
[0090] 0.6 g of 3-glycidyloxypropyltrimethoxysilane and 4 g of europium-doped barium titanate @ZIF-67 were dispersed in 110 g of ethanol, and then refluxed at 78 ° C and pH 7 for 5 h. The precipitate was collected, washed and dried to obtain epoxy-functionalized europium-doped barium titanate @ZIF-67.
[0091] 0.7 g of epoxy-functionalized europium-doped barium titanate @ZIF-67 was added to 90 g of tetrahydrofuran, and then 6 g of surface-modified boron nitride nanorods were added, and the mixture was stirred at 60°C for 4 h. The solvent was removed by reduced pressure distillation at 45°C to obtain a ceramic-based composite filler.
[0092] 6 g of the ceramic-based composite filler was added to 110 g of dimethyl sulfoxide, and ultrasonic treatment was performed for 30 min. Then, 8.7 g of 4-cyano-1-butanethiol and 0.08 g of triethylamine were added, and the mixture was stirred and reacted at 80° C. for 6 h. After the reaction was completed, the mixture was centrifuged, and the obtained solid product was washed with dimethyl sulfoxide and then dried to obtain a modified ceramic-based composite filler.
[0093] Step (3), adding 1.9 g of pullulan to 75 g of N, N-dimethylacetamide at 85° C. and stirring for 30 min to obtain a pullulan mixed solution; diluting 0.05 g of 2-chloro-5-(trifluoromethyl)benzoyl chloride with 4 g of N, N-dimethylacetamide, and dripping it into the pullulan mixed solution at a rate of 1 mL / min in an ice-water bath while stirring, first reacting in an ice-water bath for 2 h, then reacting at room temperature for 4 h, and after the reaction is completed, concentrating the reactant by rotary evaporation to half of the original volume, then precipitating the product with acetone, washing, and drying to obtain modified pullulan;
[0094] 0.08 g of glycidyl-cage polysilsesquioxane was added to 40 g of tetrahydrofuran, and then 1.5 g of modified pullulan was added, the temperature was raised to reflux reaction for 7 hours, and the solvent was removed by reduced pressure distillation at 45° C. to obtain a composite modified pullulan;
[0095] 4.5 g of the composite modified pullulan and 0.08 g of the modified composite nanosheets were added to 150 g of N,N-dimethylformamide and stirred at room temperature for 13 h to obtain a mixed solution A; the mixed solution A was poured onto a glass plate and preheated at 40° C. for 1.2 h, then dried at 85° C. for 9 h to evaporate the solvent, and then annealed at 120° C. for 12 h to obtain an outer film with a thickness of 6.5 μm;
[0096] 4.5 g of the composite modified pullulan and 1 g of the modified ceramic-based composite filler were added to 150 g of N,N-dimethylformamide and stirred at room temperature for 13 h to obtain a mixed solution B; the mixed solution B was poured on a glass plate and preheated at 40° C. for 1.2 h, then dried at 85° C. for 9 h to evaporate the solvent, and then annealed at 120° C. for 12 h to obtain an inner layer film with a thickness of 6.5 μm;
[0097] The inner film is sandwiched between the outer films, hot-pressed and then cooled to obtain a polymer-ceramic composite dielectric material with a three-layer structure; the hot-pressing temperature is 1890° C., the hot-pressing pressure is 17.5 MPa, and the hot-pressing time is 25 min.
[0098] The modified composite nanosheets used in the above-mentioned Examples 2-4 are the modified composite nanosheets prepared in Example 1.
[0099] Comparative Example 1
[0100] Compared with Example 4, in the process of preparing the outer film in Comparative Example 1, modified zinc oxide nanosheets are used instead of modified composite nanosheets, that is, nano-copper oxide is not deposited on the zinc oxide nanosheets in this comparative example, and the preparation method of modified zinc oxide nanosheets is the same as the preparation method of modified composite nanosheets, except that the composite nanosheets are replaced by zinc oxide nanosheets during the preparation process, and other conditions remain unchanged.
[0101] Comparative Example 2
[0102] Compared with Example 4, in Comparative Example 2, during the process of preparing the outer film, the composite nanosheets were used instead of the modified composite nanosheets, and other conditions remained unchanged.
[0103] Comparative Example 3
[0104] Compared with Example 4, in the process of preparing the ceramic-based composite filler in Comparative Example 3, epoxy-functionalized barium titanate @ZIF-67 is used instead of epoxy-functionalized europium-doped barium titanate @ZIF-67, that is, barium titanate is not doped with europium in this comparative example, and other conditions remain unchanged.
[0105] Comparative Example 4
[0106] Compared with Example 4, in the process of preparing the ceramic-based composite filler in Comparative Example 4, epoxy-functionalized europium-doped barium titanate is used instead of epoxy-functionalized europium-doped barium titanate@ZIF-67, that is, the ceramic-based composite filler in this comparative example does not contain ZIF-67, and other conditions remain unchanged.
[0107] Comparative Example 5
[0108] Compared with Example 4, in the process of preparing the modified ceramic-based composite filler in Comparative Example 5, epoxy-functionalized europium-doped barium titanate @ZIF-67 is used to replace the ceramic-based composite filler, that is, the modified ceramic-based composite filler in this comparative example does not contain surface-modified boron nitride nanorods, and other conditions remain unchanged.
[0109] Comparative Example 6
[0110] Compared with Example 4, in Comparative Example 6, during the process of preparing the inner layer film, a ceramic-based composite filler is used instead of a modified ceramic-based composite filler, and other conditions remain unchanged.
[0111] Comparative Example 7
[0112] Compared with Example 4, in the process of preparing the composite modified pullulan in Comparative Example 7, pullulan was used instead of modified pullulan, and other conditions remained unchanged.
[0113] Comparative Example 8
[0114] Compared with Example 4, in Comparative Example 8, during the preparation of the inner film and the outer film, the modified pullulan was used instead of the composite modified pullulan, and other conditions remained unchanged.
[0115] In the above embodiments and comparative examples, pullulan, CAS No. 9057-02-7, molecular weight 532.49024, from Shandong Fangchang Biotechnology Co., Ltd.; Tris-HCl buffer concentration 0.01 mol / L, pH 7.0-9.0, item No. MR019, from Shanghai Yueteng Biotechnology Co., Ltd.; glycidyl - cage-shaped polysilsesquioxane (OG-POSS), molecular weight 1338.00, refractive index 1.51, density 1.25g / mL, from Forsman Technology (Beijing) Co., Ltd.
[0116] Experimental example
[0117] The performance of the polymer-ceramic composite dielectric materials prepared in Examples 2-4 and Comparative Examples 1-8 was tested.
[0118] 1. Dielectric properties: The dielectric constants of each group of samples at 25°C and 150°C were tested by an LCR tester (IVYTECH, LCR6600A).
[0119] 2. Breakdown strength: Through the voltage breakdown tester (E b , -50kV) to test the breakdown strength of each group of samples at 25℃ and 150℃.
[0120] 3. Energy storage performance: The hysteresis loop of each group of samples was tested using a ferroelectric tester to obtain the electric displacement and residual polarization values, and the maximum discharge energy density of each group of samples was calculated.
[0121] The test results are shown in Table 1:
[0122] Table 1
[0123]
[0124] It can be seen from the test results in Table 1 that the polymer-ceramic composite dielectric materials prepared in Examples 2-4 of the present invention have excellent dielectric properties, energy storage properties and heat resistance. From the comparison between Comparative Example 1 and Example 4, it can be seen that the pnp heterostructure formed by copper oxide and zinc oxide on the surface of the composite nanosheet helps to reduce the dielectric loss of the outer film and improve its breakdown strength, dielectric constant and energy storage performance; from the comparison between Comparative Example 2 and Example 4, it can be seen that carboxyl groups and organic chains are introduced into the composite nanosheet after modification, and the carboxyl groups are combined with the cyano groups in the composite modified pullulan polysaccharide through strong electrostatic interaction, thereby improving the dispersibility and interfacial compatibility between the modified composite nanosheet and the modified pullulan polysaccharide; improving the composite nanosheet. The effect of rice flakes, organic chains and composite modified pullulan cross-linked, improve the cross-linking density of the outer film, thereby improving its heat resistance; from the comparison of comparative examples 3-5 and example 4, it can be seen that doping with europium can improve the dielectric properties of barium titanate-based ceramic materials, and a ZIF-67 buffer layer is generated on the surface of europium-doped barium titanate, which improves the performance of the inner film, thereby improving the dielectric properties and energy storage performance of the polymer-ceramic composite dielectric material; boron nitride nanomaterials have high insulation, pressure resistance and thermal conductivity, thereby giving the polymer-ceramic composite dielectric material The composite dielectric material has better dielectric properties and heat resistance; from the comparison between comparative example 6 and embodiment 4, it can be seen that the modified ceramic-based composite filler is obtained by modifying the ceramic-based composite filler with 4-cyano-1-butanethiol, and 4-cyano-1-butanethiol introduces cyano groups on the surface of the ceramic-based composite filler, which are covalently cross-linked with the cyano groups in the composite modified pullulan during the heating process, thereby improving the dispersibility and interface compatibility between the ceramic-based composite filler and the modified pullulan, thereby improving the performance of the polymer-ceramic composite dielectric material; from the comparative example From the comparison of 7-8 with Example 4, it can be seen that the present invention modifies pullulan by 2-chloro-5-(trifluoromethyl)benzoyl chloride, introduces cyano and trifluoromethyl polar groups, reduces the hydrophilic hydroxyl group during the modification process, and the hydrophobic trifluoromethyl group leads to low hygroscopicity. The introduction of benzene ring can improve the heat resistance of pullulan. Furthermore, the POSS structure is introduced into the modified pullulan. The low polarizability, cage structure, and heat-resistant rigid skeleton of POSS improve the comprehensive performance of the inner film and the outer film.
[0125] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a polymer-ceramic composite dielectric material, characterized in that: The following steps are involved: Step (1), preparing boron nitride nanorods using boric acid and melamine as raw materials, and then modifying with polydopamine to obtain surface-modified boron nitride nanorods; Step (2), preparing europium-doped barium titanate using barium carbonate, titanium dioxide and europium oxide as raw materials, and treating with polyvinyl pyrrolidone to obtain pretreated europium-doped barium titanate; and then preparing europium-doped barium titanate@ZIF-67 using pretreated europium-doped barium titanate, cobalt nitrate hexahydrate and 2-methylimidazole as raw materials; Europium-doped barium titanate@ZIF-67 was modified with 3-glycidyloxypropyltrimethoxysilane and then combined with surface-modified boron nitride nanorods to obtain a ceramic-based composite filler; the ceramic-based composite filler was modified with 4-cyano-1-butanethiol to obtain a modified ceramic-based composite filler; Step (3), reacting pullulan with 2-chloro-5-(trifluoromethyl)benzoyl chloride to obtain modified pullulan; reacting glycidyl-cage polysilsesquioxane with modified pullulan to obtain composite modified pullulan; Adding the composite modified pullulan and the modified composite nanosheets into N,N-dimethylformamide to obtain a mixed solution A, casting the mixed solution into a film to obtain an outer film; Adding the composite modified pullulan and the modified ceramic-based composite filler into N,N-dimethylformamide to obtain a mixed solution B, casting the mixed solution into a film, and obtaining an inner layer film; The inner film is sandwiched between the outer films, hot-pressed and then cooled to obtain a polymer-ceramic composite dielectric material with a three-layer structure.
2. The method for preparing a polymer-ceramic composite dielectric material according to claim 1, characterized in that: In the step (1), the preparation method of the surface modified boron nitride nanorods is as follows: adding boric acid to deionized water, stirring at 70-80°C until completely dissolved, adding melamine, stirring at a speed of 400-500r / min for 20-40min, and then drying at 60-80°C for 10-16h to obtain a white solid; heating the white solid to 900-1100°C in a nitrogen atmosphere at a heating rate of 5°C / min, calcining for 3-5h, and naturally cooling to room temperature to obtain boron nitride nanorods; wherein the mass ratio of boric acid, deionized water, and melamine is (4-6):(100-120):(2.7-5.4); Boron nitride nanorods are added to Tris-HCl buffer, and the pH is adjusted to 7.8-8.5 with a sodium hydroxide aqueous solution with a concentration of 0.1 mol / L, ultrasonically dispersed for 1-3 hours, and then dopamine hydrochloride is added, stirred for 10-15 hours, centrifuged, washed, and dried to obtain surface-modified boron nitride nanorods; wherein the amount ratio of boron nitride nanorods, Tris-HCl buffer, and dopamine hydrochloride is (0.4-1) g: (200-500) mL: (0.8-2) g.
3. The method for preparing a polymer-ceramic composite dielectric material according to claim 1, characterized in that: In the step (2), the preparation method of europium-doped barium titanate @ZIF-67 is as follows: barium carbonate, titanium dioxide and europium oxide are mixed and ground for 10-20 minutes, then ground with ethanol for 30-50 minutes, and then dried at 35-45°C for 5-7 hours to obtain a mixed precursor, wherein the mass ratio of barium, europium and titanium in the mixed precursor is 13.1:(0.2-0.4):4.8; the mixed precursor is heated to 950-1050°C at a heating rate of 5°C / min and calcined for 11-13 hours, and then cooled to room temperature at a cooling rate of 5°C / min, and the above calcination process is repeated 2-3 times, and ground to obtain europium-doped barium titanate; The europium-doped barium titanate is added to ethanol and ultrasonically dispersed for 50-80 minutes, polyvinyl pyrrolidone is added, and ultrasonic dispersion is continued for 60-90 minutes, and then stirred at a speed of 500-600 r / min at room temperature for 3-4 hours, centrifuged, washed, and dried to obtain pretreated europium-doped barium titanate; wherein the mass ratio of europium-doped barium titanate, ethanol, and polyvinyl pyrrolidone is (3-5):(400-500):(5-10); The pretreated europium-doped barium titanate is added to methanol and ultrasonically dispersed for 50-80 minutes, cobalt nitrate hexahydrate is added, and stirred at a speed of 500-600 r / min for 1-1.5 hours, and then a 2-methylimidazole / methanol solution with a concentration of 0.066 g / mL is added, and the reaction is stirred at room temperature for 22-26 hours, centrifuged, washed and dried to obtain europium-doped barium titanate@ZIF-67; wherein the mass ratio of the pretreated europium-doped barium titanate, methanol, cobalt nitrate hexahydrate, and 2-methylimidazole / methanol solution is (4-6):(400-500):(29.1-49.5 g):(428-715).
4. The method for preparing a polymer-ceramic composite dielectric material according to claim 1, characterized in that: In the step (2), the preparation method of the modified ceramic-based composite filler is as follows: 3-glycidyloxypropyltrimethoxysilane and europium-doped barium titanate @ZIF-67 are dispersed in ethanol, and then refluxed for 4-6 hours at a temperature of 75-80°C and a pH of 4-10, and the precipitate is collected, washed and dried to obtain epoxy-functionalized europium-doped barium titanate @ZIF-67; wherein the mass ratio of 3-glycidyloxypropyltrimethoxysilane, europium-doped barium titanate @ZIF-67, and ethanol is (0.4-0.8):(3-5):(100-120); Adding epoxy-functionalized europium-doped barium titanate @ZIF-67 to tetrahydrofuran, and then adding surface-modified boron nitride nanorods, stirring and reacting at 55-65°C for 3.5-4.5h, and removing the solvent by reduced pressure distillation at 40-50°C to obtain a ceramic-based composite filler; wherein the mass ratio of epoxy-functionalized europium-doped barium titanate @ZIF-67, tetrahydrofuran, and surface-modified boron nitride nanorods is (0.5-0.9):(80-100):(4-8); The ceramic-based composite filler is added to dimethyl sulfoxide, ultrasonically treated for 20-40 minutes, and then 4-cyano-1-butanethiol and triethylamine are added, and the reaction is stirred at 75-85°C for 5-7 hours. After the reaction is completed, centrifugation is performed, and the obtained solid product is washed with dimethyl sulfoxide and then dried to obtain a modified ceramic-based composite filler; wherein the mass ratio of the ceramic-based composite filler, dimethyl sulfoxide, 4-cyano-1-butanethiol, and triethylamine is (5-7):(100-120):(5.8-11.5):(0.05-0.1).
5. The method for preparing a polymer-ceramic composite dielectric material according to claim 1, characterized in that: In the step (3), the preparation method of the composite modified pullulan is as follows: at 80-90° C., pullulan and N,N-dimethylacetamide are mixed in a mass ratio of (1.3-2.6): (50-100), and stirred for 20-40 minutes to obtain a pullulan mixed solution; 2-chloro-5-(trifluoromethyl)benzoyl chloride and N,N-dimethylacetamide are diluted and mixed in a mass ratio of (0.03-0.06): (3-5), and stirred in an ice water bath. The reaction mixture is added dropwise into the pullulan mixture at a rate of 0.5-1.5 mL / min, first reacted in an ice water bath for 1.5-2.5 h, then reacted at room temperature for 3.5-4.5 h, and after the reaction, the reactant is concentrated by rotary evaporation to half of the original volume, and then the product is precipitated with acetone, washed, and dried to obtain modified pullulan; wherein the mass ratio of pullulan to 2-chloro-5-(trifluoromethyl)benzoyl chloride is (1.3-2.6):(0.03-0.06); Add glycidyl-cage polysilsesquioxane to tetrahydrofuran, then add modified pullulan, heat to reflux for reaction for 6-8h, and remove the solvent by reduced pressure distillation at 40-50°C to obtain a composite modified pullulan; wherein the mass ratio of glycidyl-cage polysilsesquioxane, tetrahydrofuran, and modified pullulan is (0.05-0.1):(30-50):(1-2).
6. The method for preparing a polymer-ceramic composite dielectric material according to claim 1, characterized in that: In the step (3), the outer film is prepared by mixing the composite modified pullulan, the modified composite nanosheets and N,N-dimethylformamide in a mass ratio of (3-6):(0.06-0.09):(100-200), stirring at room temperature for 10-16 hours to obtain a mixed solution A; pouring the mixed solution A on a glass plate and preheating at 38-42°C for 1-1.5 hours, then drying at 80-90°C for 8-10 hours, and then annealing at 115-125°C for 10-14 hours to obtain an outer film with a thickness of 5-8 μm; The preparation method of the inner film comprises the following steps: mixing a composite modified pullulan, a modified ceramic-based composite filler and N,N-dimethylformamide in a mass ratio of (3-6):(0.08-1.2):(100-200), stirring at room temperature for 10-16 hours to obtain a mixed solution B; pouring the mixed solution B on a glass plate and preheating at 38-42° C. for 1-1.5 hours, then drying at 80-90° C. for 8-10 hours, and then annealing at 115-125° C. for 10-14 hours to obtain an inner film with a thickness of 5-8 μm.
7. The method for preparing a polymer-ceramic composite dielectric material according to claim 1, characterized in that: In the step (3), the hot pressing molding conditions are as follows: the hot pressing temperature is 180-200°C, the hot pressing pressure is 15-20Mpa, and the hot pressing time is 20-30min.
8. The method for preparing a polymer-ceramic composite dielectric material according to claim 1, characterized in that: In the step (3), the method for preparing the modified composite nanosheet comprises the following steps: Step S1, preparing a zinc acetate aqueous solution with a concentration of 0.06 mol / L and a sodium hydroxide aqueous solution with a concentration of 1.25 mol / L, and under stirring, dripping the sodium hydroxide aqueous solution into the zinc acetate aqueous solution at a rate of 0.5-1.5 mL / min, standing and settling for 5-7 hours, centrifuging, washing, and drying to obtain zinc oxide nanosheets; wherein the volume ratio of the sodium hydroxide aqueous solution to the zinc acetate aqueous solution is (2-2.8):(9-24); Add zinc oxide nanosheets to a 1.5 mol / L copper acetate aqueous solution, stir for 20-40 min, filter, and calcine the resulting solid product in air at 280-320° C. for 1.5-2.5 h to obtain composite nanosheets; wherein the amount ratio of zinc oxide nanosheets to copper acetate aqueous solution is (3-8) g: (50-80) mL; Step S2, adding the composite nanosheets to a methanol aqueous solution, then adding (3-mercaptopropyl)trimethoxysilane, ultrasonically treating for 20-40 minutes, reflux reacting at 65-75° C. for 1.5-2.5 hours, centrifuging, washing and drying to obtain functionalized composite nanosheets; wherein the mass ratio of methanol to water in the methanol aqueous solution is 7:2; the mass ratio of the composite nanosheets, the methanol aqueous solution and (3-mercaptopropyl)trimethoxysilane is (3-5):(74.6-112):(10-15); The functionalized composite nanosheets are added to ethanol, ultrasonically dispersed for 20-40 minutes, heated to 50-80°C, and then 5-hexenoic acid and azobisisobutyronitrile are added, stirred for reaction for 3-5 hours, and after the reaction is completed, centrifuged, washed, and dried to obtain modified composite nanosheets; wherein the mass ratio of the functionalized composite nanosheets, ethanol, 5-hexenoic acid, and azobisisobutyronitrile is (4-8):(80-100):(0.4-1.6):(0.08-0.1).
9. A polymer-ceramic composite dielectric material prepared by the method for preparing a polymer-ceramic composite dielectric material according to any one of claims 1 to 8.
10. Application of the polymer-ceramic composite dielectric material according to claim 9 to capacitors.
Citation Information
Patent Citations
Polymer-base ceramic composite dielectric material and preparation method thereof
CN102173155B
Cited By
Preparation method of BOPP (Biaxially-oriented Polypropylene) film based on self-assembly coating modification
CN122563137A
A method for preparing a biaxially oriented polypropylene (BOPP) film based on self-assembled coating modification
CN122563137B